Factors affecting psychological commitment and loyalty to parks and other forms of protected areas in Canada. Issue 1 (2nd January 2023) - Mock, Steven E.; Halpenny, Elizabeth; Koroll, Rebecca; Blye, Clara Jane; Eagles, Paul F. J.; Flannery, Dylan; Lemieux, Chris; Doherty, Sean
ABSTRACT: We use a model of psychological commitment to better understand the diverse motivations that enhance behavioural loyalty to parks and protected areas. Psychological commitment reflects the degree to which an individual identifies with, wants to learn about, and chooses freely to engage with a particular phenomenon, and these factors, in turn, lead to greater loyalty and resistance to alternatives. With data collected from 634 park visitors in Alberta, Canada, we tested demographic variation and motivations that may be linked to this process of commitment. Women were more likely than men to see park visits as a reflection of their identities and also had a greater sense of volition regarding park visits. Older adults wanted to know more about the parks and also had a greater overall level of commitment. Psycho-social, spiritual, and economic motivations varied in terms of their associations with commitment, but these associations were always positive. Few variations in motivations by demographic characteristics were found. Finally, a combined assessment of commitment was associated with greater behavioural loyalty (e.g. duration and number of park visits). Park agencies can use these findings to attract and retain visitors and facilitate park experiences, with special emphasis on motives and demographic variations.